Panniculitis in childhood-onset systemic lupus erythematosus: a multicentric cohort study - Verdier, Mônica (2019)
OBJECTIVE: To evaluate prevalence, clinical manifestations, laboratory abnormalities, treatment and outcome in a multicenter cohort of childhood-onset systemic lupus erythematosus (cSLE) patients with and without panniculitis. METHODS: Panniculitis was diagnosed due to painful subcutaneous nodules and/or plaques in deep dermis/subcutaneous tissues and lobular/mixed panniculitis with lymphocytic lobular inflammatory infiltrate in skin biopsy. Statistical analysis was performed using Bonferroni correction(p < 0.004). RESULTS: Panniculitis was observed in 6/847(0.7%) cSLE. Painful subcutaneous erythematosus and indurated nodules were observed in 6/6 panniculitis patients and painful subcutaneous plaques in 4/6. Generalized distribution was evidenced in 3/6 and localized in upper limbs in 2/6 and face in 1/6. Cutaneous hyperpigmentation and/or cutaneous atrophy occurred in 5/6. Histopathology features showed lobular panniculitis without vasculitis in 5/6(one of them had concomitant obliterative vasculopathy due to antiphospholipid syndrome) and panniculitis with vasculitis in 1/6. Comparison between cSLE with panniculitis and 60 cSLE without panniculitis with same disease duration [2.75(0-11.4) vs. 2.83(0-11.8) years,p = 0.297], showed higher frequencies of constitutional involvement (67% vs. 10%,p = 0.003) and leukopenia (67% vs. 7%,p = 0.002). Cutaneous atrophy and hyperpigmentation occurred in 83% of patients. CONCLUSIONS: Panniculitis is a rare skin manifestation of cSLE occurring in the first three years of disease with considerable sequelae. The majority of patients have concomitant mild lupus manifestations.